BIOSYNTHESIS AND BIOSYNTHETIC PATHWAYS OF PENTOSES IN ESCHERICHIA COLI - Sable, Henry Z. (1962)
Sable, Henry Z. (Western Reserve University, Cleveland, Ohio) and Elayne E. Cassisi. Biosynthesis and biosynthetic pathways of pentoses in Escherichia coli. J. Bacteriol. 84:1169–1172. 1962.—Resting glucose-adapted Escherichia coli supplied with glucose continues to synthesize pentose by the oxidative pathway characteristic of logarithmically growing glucose-adapted cells. This behavior is unlike that of acetate-adapted resting E. coli supplied with glucose, which continues to synthesize most of its pentose by the nonoxidative pathway characteristic of acetate-adapted cells. When infected with bacteriophage T2H, E. coli continues to use the oxidative pathway predominantly. This finding is in contrast to reports that infection with T6r+ bacteriophage increases the participation of a nonoxidative pathway. Resting glucose-adapted E. coli supplied with acetate-1-C(14) as sole carbon source synthesizes pentose by a pathway or pathways which cannot be assessed completely by methods previously developed (which are based on the relative labeling of C-1, C-2, and C-3 of the pentose) but which is most probably predominantly nonoxidative.